Productividad de la vaca a dos edades de destete de sus crías en el Piedemonte Llanero, 1. Análisis de pesos ajustados y edad al primer parto de las crías. (1988)
At the Regional Research Center "La Libertad" of ICA in Villavicencio, the offspring of 183 cows of San Martinero, CebU and Angus-San Martinero breeds or cross were assigned at calving time to two weaning ages of 7 and 9 months. All cows were under grazing conditions, and had a mineral mix ad-libitum. The predominant grasses were molasses grass 30%, jaragua grass 20% and native legumineus and gramineous 50%. The calves were weighted at 210; 270; 365 and 540 days of age and these weights were adjusted for age of the calf; additionally a group of 46 heifer calves were left as replacement females, and their age at first calving was determined. These variables were analyzed by least squares procedures with the apropiate linear model for each variable that included the effect of sex and breed of the offspring, and some first order interactions. At 270 days the calves weaned at 9 months of age weighted 37.3 kg more than those weaned at 7 months of age; at 365 and 540 days the difference in weight was 25.3 and 17.9 kg, respectively, in favour of the calves weaned at 9 months. In percentages this difference was 18.1% at 270 days, 11.4% at 365 and 7.0% at 540 days of age. The age at first calving of the replacement heifers dit not differ significantly between the weaning ages: the overall mean was 1.452 days. The age of the dam did not significantly affected the age of first calving of the heifers. Under grazzing conditions the decreasing differences in weight of the calves weaned at 7 and 9 months of age did not influenced the age at firts calving of heifers weaned at 7 months of age. This fact could mean that the differences were minimized under the conditions of the "Piedemonte Llanero located in the eastern region of Colombia.